Pengaruh Pemberian Silika Terhadap Pertumbuhan dan Produksi Tanaman Jagung Pulut (Zea Mays Ceratina L.) Varietas Lokal Bojonegoro - Ok Syahdana Akbar; Denna Eriani Munandar (Berkala Ilmiah Pertanian, 2023)
Maize is one of the cereal crops that produces carbohydrates after wheat and rice. Maize is the staple food in Indonesia after rice, so the need for corn plants continues to increase. Cultivation of local pulut corn has problems due to low production and limited land. The development of local rice cultivation of the Bojonegoro variety to produce plants with optimal growth and high yields can be carried out, one of which is through the provision of beneficial micro fertilizers, such as silica (SiO2). The provision of beneficial silica micro fertilizer with different doses is carried out to determine the right dose so that it can be used by maize farmers. Different methods of using silica doses can be practiced to improve photosynthetic characteristics and increase maize yields (zhiming et.al,2014). This study aims to determine the effect of micro beneficial silica fertilizer at various doses on local maize plants of the Bojonegoro variety. The research was carried out using a randomized block design with a dose of silica (SiO2) to local maize plants of the Bojonegoro variety given in 6 dose levels that 0kg/ha, 50kg/ha, 100kg/ha, 150 kg/ha, 200 kg/ha dan 250 kg/ha. The SiO2 treatment was arranged in 5 blocks so that 30 experimental units were obtained. Silica application was carried out twice at the age of 7 and 14 days after planting by sowing in a circle on the soil surface. The data were analyzed by Analysis of Variance (ANOVA) to knowing the effect of treatment. The treatments with significantly different effects were further tested with using Duncan’s multiple range test (DMRT) with =5%. The research aims knowing the best dose of Silika (SiO2) at different levels gave a positive effect on increasing the variables of plant chlorophyll count, stem diameter, root fresh weight, crown fresh weight, total fresh weight, flowering age, ear diameter, ear weight, ear length, seed weight, weight 100 seeds, number of stomata, and production potential. The best dose of silica treatment on plant seed weight, namely at 50 kg/ha to 100 kg/ha produced the best seed weight in the range of 75.06 to 84.66 g, which was significantly different from the control and other treatment doses.